Analisis Faktor Yang Mempengaruhi Peningkatan Kualitas Permukiman Kumuh Mojosongo Ditinjau dengan Konsep Livability - Oktavia, Siti Devi; Suminar, Lintang; Kusumastuti (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2024)
Rapid population growth in Surakarta, coupled with inadequate land availability, has resulted in crowded and uninhabitable settlements, which adversely affect sustainability and livability. This research examines the concept of livability which reflects the quality of life of residents influenced by the resilience of the environment in meeting physical and non-physical needs. Key comfort factors include economic, social, building quality, environmental, and infrastructure elements. This research focuses on the Mojosongo slum area, which has a high level of density and is close to the center of economic activity. Although the government has successfully reduced the number of slums from 18 to 6 slums in Mojosongo, further analysis of the factors influencing the improvement of slum quality is still needed. This research uses a deductive approach with descriptive quantitative research methods and factor analysis techniques, data collected from 84 respondents through proportional random sampling. The results showed that there are 3 factors that significantly influence the improvement of Mojosongo slum quality, namely basic environmental infrastructure factors, building legality status factors and socio-economic factors.